Prime risks: the politics of pain and suffering in Spanish crisis cinema. - Allbritton, Dean (Journal of Spanish Cultural Studies)
This essay analyzes recent Spanish cinema that addresses the economic crisis, taking particular note of the ways that physical vulnerability is utilized as a metaphor for political and social precarity. I focus on three films in particular in order to highlight the metaphors of contemporary vulnerability to the Crisis:Chispa de la vida(2012),5 metros cuadrados(2012) andLos últimos días(2012). By repeatedly exposing their protagonists to lasting physical damage, debility and death, these films underscore the metaphor that is already at work and present in the signification of political vulnerability. Tracing these ties, this essay seeks to locate the impulse behind the metaphors of physical vulnerability produced within recent “crisis cinema” in Spain and to understand what happens to the fantasy of collective vulnerability and community when facing the duress of contemporary precarity.